2014
DOI: 10.1115/1.4028105
|View full text |Cite
|
Sign up to set email alerts
|

Blood Damage Through a Bileaflet Mechanical Heart Valve: A Quantitative Computational Study Using a Multiscale Suspension Flow Solver

Abstract: Bileaflet mechanical heart valves (BMHVs) are among the most popular prostheses to replace defective native valves. However, complex flow phenomena caused by the prosthesis are thought to induce serious thromboembolic complications. This study aims at employing a novel multiscale numerical method that models realistic sized suspended platelets for assessing blood damage potential in flow through BMHVs. A previously validated lattice-Boltzmann method (LBM) is used to simulate pulsatile flow through a 23 mm St. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…The TAWSS distribution for cases N, SLP, and NSLP has similar patterns and values except for the elevated values near the top of the ascending aorta on the non‐sinus wall for SLP and on the sinus side for NSLP. The values of the accumulation of viscous shear stress for the normal case are in good agreement with those reported by Min Yun et al OSI distribution displays an interesting change between SLP, NSLP and the normal case, where elevated OSI value regions (~0.5) followed by a steep drop are noticeable in the ascending aorta in SLP (sinus side wall) and NSLP (non‐sinus side wall). The BLP case leads to a similar TAWSS distribution on both walls with a peak value occurring a bit downstream of the sinotubular junction (~x/D = 1.44).…”
Section: Resultssupporting
confidence: 89%
“…The TAWSS distribution for cases N, SLP, and NSLP has similar patterns and values except for the elevated values near the top of the ascending aorta on the non‐sinus wall for SLP and on the sinus side for NSLP. The values of the accumulation of viscous shear stress for the normal case are in good agreement with those reported by Min Yun et al OSI distribution displays an interesting change between SLP, NSLP and the normal case, where elevated OSI value regions (~0.5) followed by a steep drop are noticeable in the ascending aorta in SLP (sinus side wall) and NSLP (non‐sinus side wall). The BLP case leads to a similar TAWSS distribution on both walls with a peak value occurring a bit downstream of the sinotubular junction (~x/D = 1.44).…”
Section: Resultssupporting
confidence: 89%
“…Future CFD studies can explore new heart valve designs and structural materials and determine how blood-material interactions and hemodynamics can be affected by design changes [ 61 ] with the aim of reducing thrombo-embolic complications associated with these valves, which can lead to improved valve designs. For example, analysis of blood flow characteristics through a BMHV especially around the valve hinge regions can help identify conditions that may increase the risk of blood cell damage [ 22 , 23 ]. An investigation of the effect of the leaflet opening angles on the blood flow also suggested that the opening angle can highly affect the flow downstream of BMHV and that opening angles >80 degrees would be more effective in reducing flow resistance and vortical structures [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Computational fluid dynamics (CFD), along with fluoroscopic or Doppler measurements, have the potential to provide clinically important insights by providing unprecedented hemodynamic detail for prosthetic heart valves [ 17 ]. For example, analysis of blood flow characteristics such as velocity, vortex formation, and turbulent stresses, especially around the valve hinge regions [ 18 , 19 , 20 , 21 ] can help identify conditions that may increase the risk of blood cell damage [ 22 , 23 , 24 ]. Critical turbulent shear stress thresholds of 400 N·m −2 [ 25 ] and 800 N·m −2 [ 26 ] for blood cell damage were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, Morbiducci et al ( 2009 ), Alemu et al ( 2010 ), and Min Yun et al ( 2014 ) used computational models of bileaflet MHV to study shear-induced platelet activation. The computational study by Hedayat et al ( 2017 ) compared platelet activation in the turbulent flow fields past bileaflet MHV with a model of a BHV and found that the activation potential is higher for MHV.…”
Section: Introductionmentioning
confidence: 99%